Salter Innominate Osteotomy in the Treatment of Congenital Hip Dislocation - A Long-Term Review - Gulman, B; Tuncay, Ic; Dabak, N; Karaismailoglu, N (Lippincott-Raven Publ, 1994)
We reviewed 39 patients with 52 congenitally dislocated hips, all managed by open reduction and Salter's innominate osteotomy. Mean follow-up period was 13 years (range, 8 to 25 years); 78.9% of the hips had a good or excellent clinical result, and 71.1% were good or excellent radiologically. The patients who underwent Salter's innominate osteotomy before the age of 4 had better clinical and radiological results (88.4 and 81.4%, respectively). The radiographs of the unilateral normal hips were compared to the surgically treated hips according to their acetabular index angles, center-edge angles of Wiberg, and femoral neck-shaft angles. No statistical differences were found between these two groups. The Bucholz-Ogden classification was used for the diagnosis and classification of avascular necrosis. The late radiographic signs of types 2, 3, and 4 avascular necrosis were seen in 34.6% of this series. The results show that Salter's innominate osteotomy provides good lateral coverage of the femoral head. The results are better if the operation is performed between the ages 18 months and 4 years.
Keywords: Congenital Dislocation of the Hip; Salter Innominate Osteotomy